Protecting the spouses’ interest (maslahah) in cases of defects through the application of the Islamic principle of Harm - Tengku Muda, Tengku Fatimah Muliana; Mohd, Azizah; Md Hashim, Noraini (HRMARS, 2017)
Two crucial elements serve as the objective of Islamic legal rulings are the achievement of interest (maslahah) and the repulsion of harm (mafsadah). This paper seeks to examine the juristic views of different schools of laws in Islam on the application of the Islamic principle of harm in protecting the interest of spouses in cases of defects. For comparative purpose, the paper has also discussed the provisions of law related to defects as applied in Jordan, Egypt and Morocco. Using content analysis method, the findings indicate that where either spouses is inflicted with certain types of defects, dissolution of marriage is allowed based on the ground of protecting the interest of the spouses as well as an appraisal to the Islamic principle of repulsion of harm. Keywords: Harm, Defect, Marital Life, Islamic Law, Maslahah